Overrepresentation of Indigenous youth in Canada’s Criminal Justice System: Perspectives of Indigenous young people - Cesaroni, Carla; Grol, Chris; Fredericks, Kaitlin (Australian & New Zealand Journal of Criminology, 2019)
The central purpose of this study was to provide a platform for Indigenous young peoples’ opinions regarding the overrepresentation of Indigenous young people in the criminal justice system. Specifically, the study sought (a) their thoughts on broader issues that contribute to the overrepresentation of young people, and (b) strategies on how to reduce the overrepresentation of young people in the future. Results mirrored themes and findings from the research literature. However, the results are themes that are derived from the lived and observed experiences of Indigenous young people and the Anishinaabe, Haudenosaunee, and Métis communities.